An evolutionary concept analysis of secondary traumatic stress in nurses - Arnold, Tracey (Nursing Forum, 2020)
Purpose The purpose of this article is to provide conceptual clarification of secondary traumatic stress (STS) in nurses. Background As an empathetic helping profession, nurses are at increased risk for STS. Interchangeable usage of related terms among multidisciplinary literature has resulted in lack of conceptual clarity resulting in conflation of terms. Conceptual clarity is necessary for a foundation for further research on treatment. Methods Rodgers' evolutionary model of concept analysis. Results Nurses are predisposed to STS due to exposure, empathy, bonding, and personal factors. Essential attributes were found to be posttraumatic stress disorder-like symptoms, biological symptoms, social symptoms, and psychological symptoms. Resultant consequences included an altered worldview, interpersonal difficulties, and decreased occupational commitment. Conclusion This concept analysis, the first focusing on STS, provides conceptual clarity and a concept map of STS within the nursing population.
Keywords: Rodgers' evolutionary model; concept analysis; concept map; dept.nur; peer-reviewed; secondary traumatic stress